Exploring the possibility of co-operation between higher education and industries in Malaysia (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2018)
This case study attempts to explore the posibility of co-operation between Higher Education and Industries in Malaysia. It highlights on the need, importance and the problems faced by both the entities in co-operation and collaboration. Qualitative approach was used in this study. The interviews are semi-structured and are used to generate data from university deans, collage principals, company managers and chief executive officers (CEO). The issues of suitability and reliability as well as the process of sampling, administration and analysis of the instrument of data collection are discussed. In the course of the analysis and discussion, it compares the respective contribution made by the Universities and the Industries in the field of Research and Development (R&D). Moreover, it provides suggestions to improve linkages for joint-ventures and concludes that the Universities and Industries must play complementary roles for mutual benefits in terms of knowledge dissemination and innovation. It also presents the views of the different researchers on the subject and considers the merits of the various types of co-operation suggested for the universities to keep pace with the global trend in upgrading their courses in Science and Technology.Keyword: Co-operation, Higher Education, Industries